Assessment of physical activity and body weight among medical students in Banja Luka, Bosnia and Herzegovina - Suzana Savić; Larisa Gavran; Gordana Tešanović (Medicinski glasnik, 2019)
Aim: To assess obesity and weekly physical activity among medical students at the University of Banja Luka, Bosnia and Herzegovina, related to gender and years of study profile. Methods: This is a prospective, descriptive study conducted among the student population across all six years, comprised of a validated survey instrument Youth Risk Behaviour Survey Questionnaires. The study was approved by the Ethics Committee of the School of Medicine and carried out as an anonymous survey, during the winter semester of the academic year 2017/2018. Results: Of the total 601 students, the study included 543 students, 327 (60.2%) females and 216 (39.8%) males. The majority of students 337 (62.1%) had normal weight, and 13 (2.4%) had class 1 obesity. Most female students, 255 (75.7%) had normal weight, while 132 (61.1%) males were overweight. Physical inactivity was found among 349 (64.3%) students; 11 (2%) exercised regularly twice a week and 16 (2.9%) exercised five times a week. Conclusion: This study should help better understanding and identifying the onset of obesity among the students of the School of Medicine in Banja Luka and promote awareness of the obesity problem among them that would have benefit for health of this population group.
Keywords: overweight; obesity; physical inactivity; students